SDGs and Human Rights: how to measure States’ compliance? - Tascioni, Gaia (European Journal of Sustainable Development, 2016)
In September 2015 UN General Assembly approved the SDGs and all over the world the expectations focused on the new UN Development Agenda. Apparently, issues concerning Human Rights and Human security, including absence of violence, promotion of sustainable peace and accountable institutions, have been strongly taken into account during negotiations. From this perspective, the SDGs go far beyond MDGs while acknowledging a deep connection with human development. Nonetheless, the references made to human rights law in the final document are weak and fragmented. Moreover, the SDG 16, focused on security andpromotion of the rule of law, is not time- bound and does not include clear indicators related to its targets. In the light of this, the main objective of this paper is to analyse the grade of real recognition of human rights and security issues in the Post-2015 Agenda and to suggest possible indicators for SDG 16 targets based on juridical instruments. For this reason connections between SDGs and existing human rights binding norms will be assessed in order to demonstrate how the inclusion of explicit references to core treaties in the above- mentioned indicators could promote a more effective monitoring. Key Words: SDGs, Human Security, Human Rights, Human Development, Post-2015 Development Agenda